Molecular and tissue interactions governing induction of cranial ectodermal placodes - McCabe, Kathryn L. (2009)
Whereas neural crest cells are the source of the peripheral nervous system in the trunk of vertebrates, the “ectodermal placodes,” together with neural crest, form the peripheral nervous system of the head. Cranial ectodermal placodes are thickenings in the ectoderm that subsequently ingress or invaginate to make important contributions to cranial ganglia, including epibranchial and trigeminal ganglia, and sensory structures, the ear, nose, lens, and adenohypophysis. Recent studies have uncovered a number of molecular signals mediating induction and differentiation of placodal cells. Here, we described recent advances in understanding the tissue interactions and signals underlying induction and neurogenesis of placodes, with emphasis on the trigeminal and epibranchial. Important roles of Fibroblast Growth Factors, Platelet Derived Growth Factors, Sonic Hedgehog, TGFβ superfamily members, and Wnts are discussed.